Nuovi cardinali per la Chiesa - Salvini, Gianpaolo (La civiltà cattolica, 2020)
On Sunday October 25, at the end of the Angelus, Pope Francis announced the creation of 13 new cardinals, who will be appointed as such on November 28. The Pope has designated two cardinals for the Curia departments, while the others are pastors who have either distinguished themselves in the defense of the lowliest and most needy, or who come from particularly wounded Churches, or who are very symbolic personalities.